2022
DOI: 10.1002/smll.202203335
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Metal–Support Interaction Triggering Interfacial Charge Polarization over CuPd/N‐Doped‐C Nanohybrids Drives Selectively Electrocatalytic Conversion of Nitrate to Ammonia

Abstract: The data that support the findings of this study are available in the supplementary material of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 67 publications
(98 reference statements)
0
39
0
1
Order By: Relevance
“…designed and synthesized metal–organic framework (MOF)‐derived bimetallic CuPd NPs/N‐doped carbon (CuPd/CN) hybrid nanoarrays (Figure 6e). 137,138 Cu and Pd possess modulated electronic structure and serve as dual active sites for catalyzing selectively EAS conversion, achieving FE NH3 of 96.16% and NH 3 selectivity of 92.08%. Moreover, Co‐doped Fe sites in the Fe 2 O 3 lattice (Co–Fe@Fe 2 O 3 ) form the single phase due to little structural change and transform the adsorption energy of intermediates and products, thus enhancing catalytic performance for the NO 3 RR 139 .…”
Section: Electrocatalytic Nitrate Reduction To Nh3mentioning
confidence: 99%
“…designed and synthesized metal–organic framework (MOF)‐derived bimetallic CuPd NPs/N‐doped carbon (CuPd/CN) hybrid nanoarrays (Figure 6e). 137,138 Cu and Pd possess modulated electronic structure and serve as dual active sites for catalyzing selectively EAS conversion, achieving FE NH3 of 96.16% and NH 3 selectivity of 92.08%. Moreover, Co‐doped Fe sites in the Fe 2 O 3 lattice (Co–Fe@Fe 2 O 3 ) form the single phase due to little structural change and transform the adsorption energy of intermediates and products, thus enhancing catalytic performance for the NO 3 RR 139 .…”
Section: Electrocatalytic Nitrate Reduction To Nh3mentioning
confidence: 99%
“…Consequently, there has been a dramatic growth in research efforts to study the ambient electrochemical reduction of NO 3 − to NH 3 . 15–17 However, the NO 3 − RR is an eight-electron reaction process and generates various by-products, such as NO 2 − , NO, N 2 O, N 2 , and NH 2 OH, resulting in low NH 3 selectivity, FE and yield rate. 18–20 Such electrocatalytic performance is mainly determined by the electrocatalysts; hence, the major challenge in large-scale production of NH 3 via the NO 3 − RR lies in finding a suitable catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] At present, the synthesis of NH 3 in industry mainly hinges on the traditional Haber-Bosch process (HBP). Such a reaction process is accomplished under tough operating con-ditions, including high temperature (400-550 °C) and high pressure (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), which is extremely energy-consuming. 4,5 Taking the enormous requirements into consideration (∼170 Mt per year, over 80% of total content for fertilizers), the HBP consumes 1-2% of the world's energy supply and is accompanied by extensive CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the intrinsic activity of Cu, researchers have developed various strategies to optimize its electronic state, such as by (i) engineering Cu into nanoscale or a single reaction site; , (ii) doping Cu with other elements (Pd, P, Ni and etc. ) or decorating it with a surface ligand; (iii) depositing Cu on a metal oxide support. , Among these strategies, depositing Cu on metal oxides is the most preferable one owing to the simplicity of synthesis and the considerable benefit from the strong metal–support interactions . It has been documented that metal–support interactions give rise to electron-deficient Cu species (Cu δ+ ). ,, These Cu δ+ species are more active than Cu 0 in adsorbing and activating intermediate N-species, affording a relatively low energy barrier for NO3RR. , With its excellent chemical stability and surface acidity, TiO 2 has become a well-known support for use in metal-based catalysis in various reaction systems (CO oxidation, Fischer–Tropsch process, and water–gas shift reaction); however, only a few TiO 2 –Cu catalysts have been reported for NO3RR. , On the other hand, Deng et al recently reported a considerably enhanced hydrogen evolution reaction on Pt when it was deposited on TiO 2 .…”
Section: Introductionmentioning
confidence: 99%